Contribuição original para a representação do efeito da distribuição de incidência de descargas atmosféricas no cálculo de desempenho de linhas de transmissão - Rafael Maia Gomes (2021)
This doctoral dissertation presents a contribution to the effect of lightning strikes distribution along transmission lines in its performance evaluation by proposing a calculation methodology for representing such effect. Traditionally, the methodologies for estimating the line performance of transmission lines consider the application of a span factor equal to 0.6, whose mathematical basis presents some simplifications in its developments. Therefore, this work proposes a methodology for representing the effect of the distribution of lightning strikes considering a Monte Carlo approach for simulating lightning strikes to line sectors based on Love's and Eriksson's attractiveness models, evaluating the current injection in such sectors and calculating the resulting overvoltages in the insulator strings using the HEM model and determining the critical currents associated with each simulated event using the DE method. This methodology calculates individual cumulative peak current distributions for each sector of the transmission line under analysis. The systematic application of this methodology led to the determination of span factors for several line and lightning conditions, indicating important trends for the lightning performance analyses, such as the increase of the span factor for higher values of grounding impedance and long spans, as well as the decrease of the span factor for increasing values of line CFO. It is also indicated the dependence of the span factor with the adopted lightning attractiveness model. However, the development of case studies reveals the trend of constant span factors for each line voltage level, with the value decreasing for higher voltage levels (from 0.8 – 138-kV lines - to 0.4 – 500-kV lines). This dissertation also proposes the modified critical current parameter for a prompt determination of the lightning performance of 138-kV lines, indicating an increase of approximately 20% in the critical current values calculated for lightning strikes concentrated only on the towers.